PRE SERVICE TEACHERS’ UNDERSTANDING OF SCIENTIFIC APPROACH - wati, atikah (Universitas Wiralodra, 2019)
This study investigated the implementation of scientific approach in apprenticeship program. It is aimed to describe and capture how pre service teachers implement scientific approach which consists of observing, questioning, exploring, associating and communicating in their teaching practice. What problems they faced during their teaching practice and how pre service teachers solve those problems. This study used a qualitative research design. The subjects of this study were three students of English Department of Wiralodra University who were doing apprenticeship program. Observation and questionnaire were used to validate the data. The findings showed that the three pre service teachers had implemented scientific approach in their teaching speaking although there still a lot of imperfectness and it can be concluded that between 1st, 2nd, and 3rd teacher candidates, the 3rd was the best to implement the scientific approach. The three pre service teachers also found problems in their teaching such in the process of questioning stage. However, both teacher candidates were able to solve the problem by  not ask too many questions to the students, but have to guide the students to ask questions to help the students do the activity independently